2019
DOI: 10.1042/cs20190479
|View full text |Cite
|
Sign up to set email alerts
|

PBI-4050 via GPR40 activation improves adenine-induced kidney injury in mice

Abstract: PBI-4050 (3-pentylbenzenacetic acid sodium salt), a novel first-in-class orally active compound that has completed clinical Phases Ib and II in subjects with chronic kidney disease (CKD) and metabolic syndrome respectively, exerts antifibrotic effects in several organs via a novel mechanism of action, partly through activation of the G protein receptor 40 (GPR40) receptor. Here we evaluate the effects of PBI-4050 in both WT and Gpr40−/− mice on adenine-induced tubulointerstitial injury, anemia and activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…PBI-4050 is an agonist of the G protein-coupled receptor 40 that has been consistently shown to reduce kidney fibrosis and inflammation in preclinical models [29,30]. We observed that PBI-4050 treatment was associated with lower levels of tubular lEVs parallel to improvement in tubular injury in adenine-fed mice [30]. Thus tubular lEVs appeared to be indicative of response to therapy in this animal model.…”
Section: Urinary Levs As Biomarkers Of Kidney Injurymentioning
confidence: 58%
See 1 more Smart Citation
“…PBI-4050 is an agonist of the G protein-coupled receptor 40 that has been consistently shown to reduce kidney fibrosis and inflammation in preclinical models [29,30]. We observed that PBI-4050 treatment was associated with lower levels of tubular lEVs parallel to improvement in tubular injury in adenine-fed mice [30]. Thus tubular lEVs appeared to be indicative of response to therapy in this animal model.…”
Section: Urinary Levs As Biomarkers Of Kidney Injurymentioning
confidence: 58%
“…We recently studied proximal tubulederived lEVs (megalin + ) in a mouse model of adenine-CKD treated with PBI-4050. PBI-4050 is an agonist of the G protein-coupled receptor 40 that has been consistently shown to reduce kidney fibrosis and inflammation in preclinical models [29,30]. We observed that PBI-4050 treatment was associated with lower levels of tubular lEVs parallel to improvement in tubular injury in adenine-fed mice [30].…”
Section: Urinary Levs As Biomarkers Of Kidney Injurymentioning
confidence: 66%
“…After 6 weeks of adenine-enriched diet, a significant decrease of renal XDH expression took place in WT and AhR −/− mice reflecting cell death. Indeed, renal apoptosis and adenine-induced PT-cell apoptosis were demonstrated in other mouse models of prolonged administration of an adenine diet [50,51]. XDH can be induced by tetrachlorodibenzo-p-dioxin, a well-known AhR agonist [52].…”
Section: Discussionmentioning
confidence: 99%
“…All mice from this group exhibited body weight loss that we can explain by the low palatability of adenine diet for mice and consequently a reduced food intake as described in numerous recent studies. [19][20][21] A high adenine diet (ranging 0.2% to 0.3%) is known to induce CKD in mice via the development of tubulointerstitial nephropathy, [22][23][24] whereas 5/6Nx is regarded as a model of nephron reduction followed by glomerulosclerosis due to hyperfiltration injury. 25 In our study, kidney histology and PCR analysis are in accordance with the literature with an increase in renal inflammation and fibrosis in adenine-fed mice and increased glomerular collagen deposition in the remnant kidney of 5/6Nx mice.…”
Section: Discussionmentioning
confidence: 99%